Edukasi Telur Omega-3 sebagai Pangan Fungsional di Dramaga, Bogor - Iman Rahayu Hidayati Soesanto; Sri Mulatsih; Yuli Retnani; Ahmad Yani; Rita Mutia (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Omega-3 egg education was held in Auditorium Jannes Humuntal Hutasoit (JJH) of the Faculty of Animal Husbandry, IPB University. The aim to increase public awareness as potential omega-3 egg consumers. There were 40 participants from Dramaga, Bogor living in surrounding IPB university. The educational was conducted in seminar followed by discussions, as well as pre- and post-tests. The topic of the seminar consisted of feed supplement to produce omega-3 eggs, nutrient content of omega-3 eggs, and its benefits for healthy and intelligence, as well as the prospects of omega-3 egg business. Pre-test was conducted before seminar, by distributing questionnaires to participants. The same questionnaires were distrbuted to participants after the seminar (post-test). The test results show that the education has increased participants knowledge of omega-3 eggs as a functional food from 3.45% to 25.34%. The factor influences the knowledge enhance is gender. After educated, the probability for women increase their knowlegde 6,67 times than man.